Magnetic field and prominences of the young, solar-like, ultra-rapid rotator AP 149. Issue Volume 15:Issue S354(2019) (June 2019) - Cang, Tianqi; Petit, Pascal; Folsom, Colin; Donati, Jean-Francois
Abstract: Young solar analogs reaching the main sequence experience very strong magnetic activity, directly linked to their angular momentum loss through wind and mass ejections. We investigate here the surface and chromospheric activity of the ultra-rapid rotator AP 149 in the young open cluster alpha Persei. With a time-series of spectropolarimetric observations gathered over two nights with ESPaDOnS, we are able to reconstruct the surface distribution of brightness and magnetic field using the Zeeman-Doppler-Imaging (ZDI) method. Using the same data set, we also map the spatial distribution of prominences through tomography of H-alpha emission. We find that AP 149 shows a strong cool spot and magnetic field closed to the polar cap. This star is the first example of a solar-type star to have its magnetic field and prominences mapped together, which will help to explore the respective role of wind and prominences in the angular momentum evolution of the most active stars.